2023
DOI: 10.1002/adfm.202305940
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Versus Negative Effects of Defect Engineering for Solar Water Splitting: A Review

Yulong Huang,
Linxing Meng,
Weiwei Xu
et al.

Abstract: Although defect design is an essential means of improving the performance of photocatalytic materials, defect introduction is not always beneficial. Current defect engineering focuses on avoiding or modifying introduced defects to mitigate their adverse effects on solar water splitting performance. This review comprehensively summarizes the strategies for defect introduction and discusses their crucial roles in solar water splitting. Focusing on the dual effects of defects, the most basic schemes for preparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 174 publications
(260 reference statements)
0
6
0
Order By: Relevance
“…Extensive research has shown that heteroatom doping certainly introduces some detrimental defects or causes negative effects, limiting the improvement of PEC performance. [ 9 ] With an increase in the amount of selenium doping in Fe 2 O 3 , the depletion region becomes too narrow to ensure effective charge separation. [ 10 ] Excessive molybdenum doping into BiVO 4 induces the formation of new trap states, moderating the Fermi‐level pinning effect and leading to persistent recombination of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown that heteroatom doping certainly introduces some detrimental defects or causes negative effects, limiting the improvement of PEC performance. [ 9 ] With an increase in the amount of selenium doping in Fe 2 O 3 , the depletion region becomes too narrow to ensure effective charge separation. [ 10 ] Excessive molybdenum doping into BiVO 4 induces the formation of new trap states, moderating the Fermi‐level pinning effect and leading to persistent recombination of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Doping and vacancy defects in metal sulfides, especially for those introducing S vacancies or O doping, are effective strategies for enhancing carrier transport dynamics. Heteroatom doping or vacancies do not always favor carrier transport and introduce impurities that lead to severe carrier recombination and hinder photogenerated electron–hole pair transfer 18 …”
Section: Introductionmentioning
confidence: 99%
“…At present, metal oxide has attracted great attention in catalytic materials for many applications (typically energy conversion and pollutant degradation) due to their low cost, availability, chemical stability, and structural diversity. , Oxygen vacancy (Ov), as an intrinsic defect of the oxide, always appears in metal oxide crystals. Ov has been proven to tune the coordination environment, change the electronic structure, and vary the adsorption tendency of active sites, thus improving the catalytic activity of metal oxides. The introduction and regulation of Ov in a metal oxide crystal have become one research hotspot in the catalytic field. Therefore, quantification of surface Ov in metal oxide is vital for understanding the quantitative structure–activity relationship, which will provide a powerful guidance for further design and application of Ov. …”
Section: Introductionmentioning
confidence: 99%